Total Knee Arthroplasty in Patients with Parkinson's Disease: A Critical Analysis of Available Evidence - Fraz Noor, Naveed Gul, Nisar Ahmed, Zain-Ul-Abideen, Muhammad Saleem Akhtar, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the significance of total knee arthroplasty in patients with Parkinson's disease. Study design: Retrospective study. Place and duration of study: Department of Orthopaedics, Sahara Medical College, Narowal and CMH Kharian Medical College Kharian from 1st July 2020 to 30th September 2022. Methodology: Fifty patients suffered from Parkinson disease which was already diagnosed and the patients attended the Orthopaedic Ward for knee arthroplasty were included. Patients were then followed up till 12 weeks for the clinical analysis of the preoperative and postoperative outcomes of the procedure. Western-Ontario and McMaster-Universities Osteoarthritis Index, Short Form Health Survey-scale, physical component-summary as well as mental-component summary were used for the critical analysis of the patients underwent knee arthroplasty. Knee Society-Score and Knee Society-Function Score determined the deformity, stability, pain and functional analysis. Results: The mean age of the cases was 66.91 ± 6.62 years. There were more females than males in this study with a comparative percentage of 20% vs 80% respectively. There were 60% left knee arthroplasty with 22% in grade IV. Range of motion as well as stability of the patients was also improved. SF-12 also showed a significant improvement in the Physical component-summary and mental-component summary levels. There was a reduction in pain and stiffness analyzed through Western-Ontario and McMaster-Universities Osteoarthritis Index scoring and more flexion as analyzed by range of motion. Conclusion: There is better scoring of patients from pre to postoperative state although still towards lower side and with poor motor functional outcomes. Key words: Ganglion, Neurodegenerative, Arthroplasty, Significance, Analysis